2018
DOI: 10.1021/acsami.8b02225
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Osteogenic Differentiation of Stem Cells on Phase-Engineered Graphene Oxide

Abstract: Graphene oxide (GO) has attracted significant interest as a template material for multiple applications due to its two-dimensional nature and established functionalization chemistries. However, for applications toward stem cell culture and differentiation, GO is often reduced to form reduced graphene oxide, resulting in a loss of oxygen content. Here, we induce a phase transformation in GO and demonstrate its benefits for enhanced stem cell culture and differentiation while conserving the oxygen content. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…( Figure 5). On the other hand, many previous studies [94,127,128] have shown that graphene has the ability of non-covalent bonding (π-π stacking interactions), while GO has the ability to make electrostatic interactions and hydrogen bonds. The different degree of oxygen content can be mediated to change the binding capacity of growth agents (dexamethasone, β-glycerophosphate, insulin, and ascorbic acid) during the differentiation of stem cells.…”
Section: Applications Of Go Micropatternsmentioning
confidence: 96%
See 2 more Smart Citations
“…( Figure 5). On the other hand, many previous studies [94,127,128] have shown that graphene has the ability of non-covalent bonding (π-π stacking interactions), while GO has the ability to make electrostatic interactions and hydrogen bonds. The different degree of oxygen content can be mediated to change the binding capacity of growth agents (dexamethasone, β-glycerophosphate, insulin, and ascorbic acid) during the differentiation of stem cells.…”
Section: Applications Of Go Micropatternsmentioning
confidence: 96%
“…At present, many biosensor studies have explored the use of single-layered GO nanosheet as a chemical modification platform, based on the excellent hydrophilicity, electrical conductivity, specific surface area, and chemical stability of this material [91]. For example, the high specific surface area of GO (736.6 m 2 /g) is superior to conventional 2D materials (e.g., aluminum oxide, titanium, and silica) [92], making the GO surface a biologically active interface where various surface oxygen functional groups can readily bind to biomolecules [93,94]. Electrochemical measurements have been carried out to determine the properties of GO-bonded substances, including dopamine, DNA, NADH, which is an important cofactor of metabolism in all living cells, heavy metal ions, and enzymes [94].…”
Section: Advantages Of the Go Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, graphene oxide (GO) is also a promising nanomaterial with applications in biosensors because of its ease of surface modification, good biocompatibility, hydrophilicity, and sheet-like structure that provides a large surface area [72,[78][79][80][81]. Its surface also contains a series of oxygen-containing functional groups, including carboxy, epoxy, and hydroxy functional groups, which bind easily with biological targets such as antibodies and peptides to form biosensors due to the abundant oxygen functional groups.…”
Section: Application Of Nanomaterials In Microfluidic-based Systems Fmentioning
confidence: 99%
“…Up to now, the possibility of GO combined with MSC as the cell scaffold has also been initially explored. [18][19][20][21][22] However, there are few related studies and bone marrow stromal cells (BMSC) are mostly used as seed cells in the research.…”
Section: Introductionmentioning
confidence: 99%